153k views
3 votes
Subtract.

5x2 - 5+1
(2x2 +9x-6)
-_________
A. 3x2 - 4x+7

B. 3x2 - 14x+7

c. 3x2 + 4x - 5

D. 3x2 + 14x-5

User Gmagno
by
5.1k points

1 Answer

5 votes

Answer:

The answer is:
3x^2-14x+7

which agrees with answer B) among your list of possible options.

Explanation:

I think you forgot an "x" in the first trinomial, so, let's try that:


(5x^2-5x+1)-(2x^2+9x-6)=\\= 5x^2-5x+1-2x^2-9x+6=\\=3x^2-14x+7

User Gnarlybracket
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.